Teacher’s Roles and Challenges in Fostering Students’ Learning Autonomy - Asih Santihastuti; Fiska Nurrahma Oktavia (English Education Study Program, 2023)
This paper identifies the challenges of fostering students’ learning autonomy and teachers’ roles in supporting them. Thirty-one English major students participated in the study conducted in an Extensive Listening class. They were expected to plan their own learning (learning objectives, strategies, activities) and be responsible with their own learning plan. Every student wrote their self-reflection at the end of the activity to describe their experience, feelings, strengths, and weaknesses of the activities to explore areas of improvement. The analysis of the student’s reflections and the teacher’s observation suggested that most students struggled with the pre-listening activity as they could not identify their own learning objectives and strategies and follow the plan they had previously made before the listening activity. Further, this paper will discuss the result of the student’s reflections on the learning activity and how the teacher should deal with that to find the roles of the teacher in supporting learners’ autonomy.